The Effect of 16-Week Progressive Circuit Training Program on the Health and Skill-Related Fitness Parameters of Overweight University Students - Pocaan, Jordan (Physical Education Theory and Methodology, 2024)
Study purpose. This study examines the effect of a 16-week interval progressive circuit training program on the skill and health-related fitness of overweight university students. Materials and methods. A total of 72 university students underwent health and skill-related fitness tests before and after a 16-week progressive circuit training program. Paired sample t-tests and Wilcoxon signed-rank tests were used to determine differences between pre- and post-tests. Results. Significant decrease in BMI, cardiovascular endurance, agility, speed and reaction time was observed after a 16 week progressive circuit training program (p ≤ 0.05). In contrast, strength, flexibility, coordination and power increased significantly (p ≤ 0.05). The 16-week interval progressive circuit training programme has a positive effect on the physical fitness among the study participants. Conclusions. The findings encourage further research into optimized training protocols, long-term sustainability of improvements, and tailored applications for specific population groups, ultimately advancing our understanding of the multifaceted benefits of interval progressive circuit training.